Slovenian and German Competition Policy Regimes: A comparative analysis - Polk, Andreas; Primec, Andreja (Naše gospodarstvo/Our economy, 2017)
We use an institutional approach to analyze differences and similarities between competition policy regimes in Slovenia and Germany. We first indicate differences that exist in the implementation of EU competition law at the national level, given the unified framework of EU competition policy. In a next step, we discuss recent cases in both countries and indicate how historical developments and economic factors influence decision making and case law. We also discuss recent developments of the national competition policy regimes and indicate how the digital economy might shape competition policy in the future.